HYDRODYNAMICS SIMULATION IN CYLINDRICAL MICROCHANNEL FOR GASES MIXING IN ONE STEP UREA SYNTHESIS - NURRAHMAN, REZA (2015)
Miniaturizing process device is able to emerge a new development in industrial process. In urea and ammonia industries, it is used at the design stage. The major issue of microreactor study, meanwhile, is in term of the mixing and reaction in which, in this case, it is highly relied on the microreactor geometry. Microreactor is commonly in the form of microchannel. Optimizing microchannel for better fluid mixing and fluid interaction is one way to achieve an effective production with less energy consumption. On the other hand, studies for urea production in microreactor so far are not available. Urea production through one step synthesis has been proposed in which Hj, N2, and CO2 have been introduced simultaneously in the microreactor. The interest of this research is to investigate die hydrodynamics behavior of H2, N2, and C02 gas in cylindrical microchannel. Computational flow simulation was performed and Computational Fluid Dynamics used in this research method was bymeans ofthe application ofANSYS-FLUENT software.